Identifikasi Tingkat Kematangan Buah Carica dalam Pengolahan Citra Digital dengan Menggunakan Metode Transformasi Ruang Warna HSI - M. Tsaqif Daniyal Maula; Firman Santoso; Abd. Ghofur (G-Tech: Jurnal Teknologi Terapan, 2024)
Carica fruit is a fruit that is rarely found, this fruit is only found in the Dieng mountains, namely the Wonosobo-Banjarnegara area. This research aims to identify the level of maturity of carica fruit using HSI color space transformation in order to obtain better information about the level of fruit maturity in selecting fruit to be processed. In the process of identifying the ripeness of Carica fruit, 90 datasets were used. The 90 datasets are divided into 3 categories, namely, 30 cooked, 30 cooked, and 30 raw. Then, the 90 datasets were divided into 30 training data and 60 testing data. The results of the identification showed 57 correct out of 60 testing datasets with an accuracy of 95%.